Effective Strategies for Writing and Publishing Scientific Papers: A Workshop for Final-Year Students at Muria Kudus University - Rahmawati, Sri; Wahyuni, Sri; Fikri, Moh. Hilman; Fatimah, Siti; Perdana Bayu Putra, Rizky (⁠International Journal of Asia Pacific Community Service, 2025)
Scientific publication is one of the essential competencies for students in developing scientific knowledge and academic competitiveness. However, many final-year students at Muria Kudus University still face difficulties in writing and publishing scientific papers. To address this issue, this community service activity was carried out through a workshop based on Participatory Action Research (PAR), which actively involved students in discussions, hands-on practice, and intensive mentoring in scientific writing. The stages of the activity included problem identification, strategy planning, workshop implementation, and program effectiveness evaluation. A post-workshop survey showed that 85% of participants understood proper scientific writing techniques, 72% were able to prepare manuscripts according to journal standards, and 60% were ready to submit their manuscripts for publication. These findings indicate that the PAR approach is effective in improving students' understanding and skills in writing and publishing scientific papers. Through this workshop, it is expected that students will become more confident in producing high-quality scientific works and contributing to academic publications.